The Dynamics of Poverty-Environment Linkages in the Coastal Zone of Ghana - Lawson, E.T.; Gordon, C.; Schluchter, W. (Elsevier Ltd, 2012)
With a high dependence on natural resources and increasing environmental degradation as a result of climatic and non-climatic factors, poverty remains a critical socioeconomic issue in the coastal zone of Ghana. Coastal poverty is closely related to the nature and complexity of coastal ecosystems and often varies from poverty in other areas. This paper contends that adequately responding to the environmental and socioeconomic issues in the coastal zone requires assisting the poor cope with changes on the coast. In doing this it is important to appreciate how poverty is defined especially by the resource users themselves as well as the nature of the poverty–environment interactions. With women being highly dependent on coastal natural resources this paper draws on the experiences of 304 women from two communities to investigate coastal people's perception of poverty. It presents empirical evidence of poverty–environment linkages and examines implications of these linkages for the effective management of Ghana's coastal natural resources. The results show that respondents describe poverty through diversity of measures rather than solely as an absence of money. In addition their livelihood patterns revolve around the availability of some coastal natural resources. Since there is no national policy for the management of the coastal natural resources the paper concludes by recommending the development of a comprehensive Integrated Coastal Zone Management plan that incorporates the priorities and needs of local resource users, alleviates poverty whilst increasing awareness of resource users of more appropriate mechanisms for managing coastal resources.
Keywords: coastal zone; Environment; Ghana; poverty; Natural Resource Management; resource degradation